2018
DOI: 10.7150/jca.25201
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal ephrinA2 derived from serum as a potential biomarker for prostate cancer

Abstract: Up-regulation of serum ephrinA2 is common in various malignancies and has been suggested as a potential biomarker for the diagnosis and prognosis of prostate cancer (PCa). However, the type of serum ephrinA2 expressed in PCa patients remains elusive. Furthermore, the level of exosomal ephrinA2 derived from serum is increased in patients with osteoporosis, a common complication of PCa patients undergoing androgen deprivation therapy. It is unknown whether exosomes derived from PCa patient serum contains ephrinA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 23 publications
(25 reference statements)
0
24
0
Order By: Relevance
“…After detailed evaluation of the full texts, 85 articles were excluded for the following reasons: (a) 34 studies not for diagnostic research; (b) 34 studies with insufficient data; (c) 7 studies based on combined diagnosis; (d) 1 study with no difference in expression; (e) 6 studies with sample size less than 20 in either case or control group; and (f) 3 studies with non‐English full‐text. Finally, a total of 70 studies from 42 publications 15‐56 involving 3161 cases and 2763 controls were analyzed in the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After detailed evaluation of the full texts, 85 articles were excluded for the following reasons: (a) 34 studies not for diagnostic research; (b) 34 studies with insufficient data; (c) 7 studies based on combined diagnosis; (d) 1 study with no difference in expression; (e) 6 studies with sample size less than 20 in either case or control group; and (f) 3 studies with non‐English full‐text. Finally, a total of 70 studies from 42 publications 15‐56 involving 3161 cases and 2763 controls were analyzed in the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…All cancer cases were confirmed pathologically. There were fifteen cancer types: lung cancer (LC, n = 7), [15][16][17][18][19][20][21] esophageal cancer (EC, n = 1), 22 gastric cancer (GC, n = 5), [23][24][25][26][27] colorectal cancer (CRC, n = 5), [28][29][30][31][32] hepatocellular carcinoma (HCC, n = 4), [33][34][35][36] pancreatic cancer (PC, n = 3), [37][38][39] ovarian cancer (OC, n = 3), [40][41][42] glioma (n = 3), [43][44][45] clear cell renal cell carcinoma (ccRCC, n = 2), 50,51 bladder cancer (BC, n = 3), 46,48,49 prostate cancer (PCa, n = 2), 47,52 osteosarcoma (n = 1), 53 multiple myeloma (MM, n = 1), 54 melanoma (n = 1), 55 and laryngeal squamous cell carcinoma (LSCC, n = 1). 56 Publication years of all included researches range from 2013 to 2019.…”
Section: Study Characteristics and Quality Assessmentsmentioning
confidence: 99%
“…The next step would be to confirm that our method works for isolating exosomes from serum, urine and other secretions 52 . Our modified PEG method may need further refinement, such as through incorporation of an ultracentrifugation step, since transmission electron microscopy revealed that a small proportion of our exosomes had diameters >200 nm.…”
Section: Discussionmentioning
confidence: 99%
“…136 Ascites derived EV associated E-cadherin has diagnostic utility in ovarian cancer and serum EV associated EphrinA2 may aid diagnosis of prostate cancer. 137,138 There is a large number of research studies published regarding the analysis of EVs as biomarkers for cancer. To assess the EV isolation and characterization methods employed by the large number of EV studies, we selected studies based on a previous meta-analysis study that looked at the clinical signicance of EVs in cancer.…”
Section: Ev Characterizationmentioning
confidence: 99%